2016
DOI: 10.1186/s12933-016-0481-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity and epicardial fat on early left atrial dysfunction assessed by cardiac MRI strain analysis

Abstract: Background: Diastolic dysfunction is a major cause of morbidity in obese individuals. We aimed to assess the ability of magnetic resonance imaging (MRI) derived left atrial (LA) strain to detect early diastolic dysfunction in individuals with obesity and type 2 diabetes, and to explore the association between cardiac adipose tissue and LA function.Methods: Twenty patients with obesity and T2D (55 ± 8 years) and nineteen healthy controls (48 ± 13 years) were imaged using cine steady state free precession and 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
6
28
1
Order By: Relevance
“…11,12 Interestingly, changes in epicardial adipose tissue mass precede and predict the onset of diabetes, 13,14 and the degree of epicardial adiposity is closely associated with changes in diastolic filling dynamics. 15 This last finding is confirmed by Christensen et al in Diabetes, Obesity and Metabolism. 16 In addition, diabetes enhances the production of proinflammatory cytokines in epicardial adipocytes, which may adversely affect the adjoining myocardium, 17,18 and potentially, other organs.…”
Section: Role Of Epicardial Adipose Tissue Expansion and Inflammatisupporting
confidence: 57%
See 1 more Smart Citation
“…11,12 Interestingly, changes in epicardial adipose tissue mass precede and predict the onset of diabetes, 13,14 and the degree of epicardial adiposity is closely associated with changes in diastolic filling dynamics. 15 This last finding is confirmed by Christensen et al in Diabetes, Obesity and Metabolism. 16 In addition, diabetes enhances the production of proinflammatory cytokines in epicardial adipocytes, which may adversely affect the adjoining myocardium, 17,18 and potentially, other organs.…”
Section: Role Of Epicardial Adipose Tissue Expansion and Inflammatisupporting
confidence: 57%
“…Epicardial fat expands and becomes inflamed in both type 1 and type 2 diabetes; even in patients with concurrent obesity or renal disease, diabetes contributes independently to the volume of epicardial fat . Interestingly, changes in epicardial adipose tissue mass precede and predict the onset of diabetes, and the degree of epicardial adiposity is closely associated with changes in diastolic filling dynamics . This last finding is confirmed by Christensen et al in Diabetes, Obesity and Metabolism .…”
Section: Role Of Epicardial Adipose Tissue Expansion and Inflammationmentioning
confidence: 59%
“…The reported experience of using FT-CMR LA strain parameter assessment for clinical diagnosis is quite recent, and encompasses cohorts of patients undergoing atrial fibrillation catheter ablation [ 8 , 47 , 48 ], implantable cardioverter-defibrillator implant [ 47 , 49 ], community volunteers without cardiovascular disease at baseline [ 50 , 51 ], patients with acute myocarditis [ 45 ], obesity [ 52 ], and Ebstein’s anomaly [ 53 ]. These studies established the feasibility and validity of LA strain parameter measurement using CMR; and in [ 51 ] found negative correlation between LA strain and LA fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kishi et al [ 40 ] reported that high insulin resistance was associated with worse relative wall thickness and worse peak longitudinal strain and early diastolic strain rate from apical 4-chamber view, and e′, depending on obesity level from 3179 participants. Moreover, Evin et al [ 41 ] showed that left atrial strain as assessed by cardiac magnetic resonance imaging was a sensitive tool for the detection of early LV diastolic dysfunction in individuals with obesity and T2DM and correlated with BMI and epicardial fat. In this study, LV mass index and left atrial volume index in T2DM patients with overweight were significantly larger than those in T2DM patients without overweight (79 ± 21 g/m 2 vs. 71 ± 19 mg/m 2 , p < 0.05; 30 ± 9 mL/m 2 vs. 30 ± 9 mL/m 2 , p < 0.05, respectively).…”
Section: Discussionmentioning
confidence: 99%